Recycling Reinforced: The Synergistic Dynamics of Sustainable Behavior - Enginkaya, Ebru; Saglam, Munise Hayrun (MDPI, 2024)
Recent research has specifically targeted the decision-making process of eco-friendly individuals, emphasizing the significance of recycling and its impact on sustainability. Our study extends this inquiry by examining the correlation between recycling participation and pro-environmental behavior among consumers, integrating the concepts of self-efficacy, feelings of pride, and social pressure into our analysis. We utilized targeted sampling to collect data from a diverse sample of 378 participants, ensuring representation across key demographic groups. By employing Partial Least Squares-Structural Equation Modeling (PLS-SEM), we aimed to explore the intricate relationships underpinning recycling behaviors and pro-environmental actions. The results suggest that self-efficacy and feelings of pride significantly influence individuals' recycling behaviors, highlighting the role of psychological and social factors in promoting environmental sustainability. It was concluded that social pressure did not have the expected moderating effect on increasing consumers' feelings of pride and self-efficacy toward recycling activities. This study sheds light on the underlying mechanisms that drive pro-environmental actions, contributes to understanding sustainability promotion through recycling, and offers insights for policymakers and environmental advocates to help foster environmental responsibility and behavior change. The findings emphasize that individuals often value personal achievement and development more when addressing environmental responsibilities and that social pressure does not achieve its expected effects.
Keywords: pro-environmental behavior; recycling; sustainability; self-efficacy; social pressure; feelings of pride; PROTECTION MOTIVATION THEORY; PLANNED BEHAVIOR; COGNITIVE THEORY; SOCIAL-INFLUENCE; WASTE; NORMS; STRATEGIES; ATTITUDES; Science & Technology - Other Topics; Environmental Sciences & Ecology